A novel smoothed (SMO) point mutation in congenital tibial hemimelia: a case report - Xiaodong Yang; Siyu Pu; Bo Xiang; Xueyang Tang; Jing Chen (BMC, 2023)
Abstract Background Congenital tibial hemimelia (CTH [MIM: 275220]) is a rare congenital limb deficiency that manifests as a shortened, curved, dysplastic or absent tibia with polydactyly. In previous studies, mutations of a distant sonic hedgehog (SHH) cis-regulator (ZRS) and a Shh repressor (GLI3) were identified. Case presentation Here, we admitted a 20-month-old boy who manifested with right tibial deformity, varus foot, ankle dislocation, and ipsilateral preaxial polydactyly. After genetic sequencing and data analysis, the results revealed a 443 A > G mutation in the father and a 536 C > T mutation in the mother in exon 2 of the Smoothed (SMO) gene at 7q32.1, with the coexistence of both mutant alleles in the proband/patient. Conclusions Our report suggests that even though not previously reported, SMO mutations may be associated with limb anomalies such as tibial hemimelia via Hh signaling in humans and has implications for genetic counseling.